Investigating systemic inflammation and hypercoagulability in psoriasis: implications for cardiovascular disease - Visser, Maria Johanna Elizabeth (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.